The Effect Of Puzzle Playing Therapy On Anxiety Due To The Impact Of Hospitalization In Preschool Aged Children: Study Literature Review: Pengaruh Terapi Bermain Puzzle Terhadap Kecemasan Akibat Dampak Hospitalisasi Pada Anak Usia Prasekolah: Study Literature Review - Fadhilah, Vita; Wardani, Septi; Mareta, Reni (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: Hospitalization can cause anxiety in some children. The level of anxiety due to hospitalization in most preschool-age children is moderate to severe anxiety. Puzzle play therapy is a therapy that can reduce anxiety in preschool-aged children. Purpose: Identify anxiety due to hospitalization in preschool-aged children before and after playing puzzle therapy, identify the effect of playing puzzle therapy on hospitalization anxiety in preschool-aged children. Method: The method used in this study was a literature review design by collecting secondary data from Google Scholar and ScientDirect using the keywords